Market structure and performance of dual banking system in Malaysia - Mohammed, Nafisah (2018)
Concentration, competition and efficiency are three elements that are often associated with the banking industry. Banking industry in most of the countries in the world had undergone tremendous changes due to several structural changes occurred in the industry. Malaysia has also not left behind in facing this wave of change. There are four main sources that contribute to the structural changes in the Malaysian banking industry namely, bank mergers, implementation and restructuring of Islamic banking industry, liberalization and advancement in information and communication technology (ICT). Besides, the 1997 East Asian Financial Crisis and restructuring of banking industry under the Financial Sector Master Plan also have contribute to the aggressive structural changes in the Malaysian banking industry. Thus, the main purpose of this study is to investigate the impact of structural changes on the degree of concentration, competition and performance of the Islamic banking system compared to conventional banking system in Malaysia. This study used the data of both domestic and foreign banks which operated in dual banking industry in Malaysia, covered the period 1997-2016. The research method in this study has been developed properly to achieve the objectives of the study. First, this study utilizes structural approach to measure various types of market concentration indices, calculated on year-to-year basis in order to investigate the link between concentration and competition. All measures of concentration have been calculated using the formulas proposed in the industrial organizational theory. Second, this study developed the Panzar-Rosse (PR) model to calculate the Hstatistics to determine the degree of competition in Islamic and conventional banking markets. Third, the data envelopment analysis (DEA) method is used to measure income and cost efficiency scores. Finally, the calculated measures of concentration, competition and efficiency are included in a model in order to estimate the relationship between those variables. All the econometric models in this study are estimated using pooled cross-section (OLS) and panel estimation approach (fixed and random effects). Findings of this study are as follows. First, analysis on market concentration provides evidence on the decreasing trend in the level of concentration of Islamic banking market. In contrast, level of concentration is increasing in the conventional banking market. Second, the H-statistics computed using the PR model shows both banking markets operated under the monopolistic competition structure. However, level of competition is more intensifying in the Islamic compared to conventional banking market. Third, results on efficiency scores show that Islamic banks are more cost efficient, but conventional banks are more efficient in generating income. Fourth, the results on the nexus between competition, concentration and efficiency show the existence of negative relationship between competition and concentration; and a positive relationship between efficiency and competition. Based on these findings, this study concludes that the existence of an ideal level of concentration and competition is important for banks to adjust their behaviour to suit market conditions and to operate efficiently. Besides, policy makers and regulators may use the knowledge on market structure and performance in this study to formulate policies and strategies that will optimize the number of banks that operated in the industry.